Optimum Desgin Of Rectifying Circuit With Receiving Antenna For RF Energy Harvesting - Zakaria, Zahriladha; Zainuddin, N. A; Husain, Mohd Nor; Mutalib, M. A; Amilhajan, Ena; Abdullah, M. S. K.; Sam, Weng Yik (Asian Research Publishing Network (ARPN), 2016)
-